Analysis of ductile damage changes of pipelines with unconstrained dents in rebound process. (February 2021) - Wu, Ying; Zhang, Yuan; Li, Linya
Highlights: The ductile damage degree of dented pipes was studied based on the Oyane ductile fracture criterion. The change of the ductile damage integral value with the change of parameters during each loading process were analyzed. The relationship between the pipeline damage and the depth of the dent were analyzed. Abstract: Dent is one of the most common defects in mechanical damage of oil and gas pipelines. Most of the dents generated during pipeline construction are unconstrained dents, and rebound will occur during service of the pipeline. The dent defect can be considered as ductile damage. Taking X52 steel pipe as the research object, the rebound process of unconstrained dents in service is numerically simulated. Based on the Oyane ductile fracture criterion, the ductile damage degree of dented pipes affected by multiple factors was studied. The change of the ductile damage integral value with the change of parameters during each loading process of the pipeline and the relationship between the pipeline damage and the depth of the dent were analyzed. The results show that the analysis results based on the ductile damage model are in accordance with the conclusions of the existing research, and the ductile damage integral value of the pipeline changes with the depth of the dent in a reasonable law, which shows that the ductile fracture criterion can be used for the safety evaluation of dented pipeline.